Sharia Banking’s Profit Loss Finance in the Context of ASEAN Economic Community - Ningsih, Mardhiyatur Rosita (Faculty of Islamic Economics and Business, Institut Agama Islam Negeri (IAIN) Surakarta, 2016)
The paper aims to analyze the problems of profit and loss sharing financing is conducted through literature and interviews with funding customers, islamic bankers and entrepreneurs. The result show that profit oriented, lack of trust in the abilities of partners, moral hazard, mismanagement and lack of syariah product information. So, give Incentive for funding customers, incentive compatible constraint, involved effort in spiritual and intellectual expected may help small and medium enterprises to face ASEAN Economic Community. Keywords: ASEAN Economic Community, profit and loss sharing financing, small and medium enterprises